Sphaerococcus coronopifolius (Rhodophyta, Gigartinales): a Mediterranean red alga with potential and applications in restoration. Issue 7 (3rd April 2019) - Fratini, Filippo; Rivière, Catherine; Santamaria, Ulderico
Abstract: Experimental studies conducted on some species of Mediterranean red algae allowed to identify Sphaerococcus coronopifolius Stackhouse as a valid alternative to the Pacific alga Gloiopeltis furcata (Postels & Ruprecht) J. Agardh, for the extraction of a material usable as natural consolidant and adhesive in the field of restoration. Promising results have been observed by comparing the extracts obtained from these two algae after the same extraction procedure. Chemical analysis (FTIR) revealed that S. coronopifolius has qualities similar to G. furcata . Even more promising results for S. coronopifolius compared to G. furcata were observed after the analysis of pH and conductivity, and the adhesion tests carried out on both extracts. Abstract :